Strategic Planning for Islamic Educational Institutions in the Globalization Era - Muhammad Ali Murtadho; Ridho Dwi Putra; Fauza Yanuarti Pertiwi; Muhammad Sirozi (Journal of Social Work and Science Education, 2026)
Islamic educational institutions face complex challenges in the globalization era, including technological disruption, intense competition, and demands for adaptive yet values-based graduates. Strategic planning offers a potential solution, yet its integration with Islamic educational values remains underexamined. This study examines how strategic planning can address development challenges faced by Islamic educational institutions in the globalization era. A qualitative library research method was employed, analyzing 45 academic sources (books, peer-reviewed articles, policy documents) using thematic content analysis. The analytical framework integrated SWOT analysis with Islamic educational principles. Findings indicate that strategic planning addresses five key challenges: (1) human resource quality through continuous competency-based training; (2) institutional governance through systematic planning and evaluation; (3) Islamic value integration through curriculum and co-curricular alignment; (4) funding sustainability through resource optimization and partnerships; (5) graduate competitiveness through 21st-century skills development. SWOT analysis emerged as a relevant tool for context-sensitive planning. This study integrates modern strategic management concepts (SWOT, performance measurement) with Islamic educational values into a comprehensive conceptual framework. Policymakers and institutional leaders should implement systematic, values-based strategic planning to enhance institutional competitiveness while preserving Islamic identity.